Auxins and Cytokinins-The Role of Subcellular Organization on Homeostasis - Skalický, Vladimír; Kubeš, Martin; Napier, Richard; Novák, Ondřej (International journal of molecular sciences, 2018)
Plant hormones are master regulators of plant growth and development. Better knowledge of their spatial signaling and homeostasis (transport and metabolism) on the lowest structural levels (cellular and subcellular) is therefore crucial to a better understanding of developmental processes in plants. Recent progress in phytohormone analysis at the cellular and subcellular levels has greatly improved the effectiveness of isolation protocols and the sensitivity of analytical methods. This review is mainly focused on homeostasis of two plant hormone groups, auxins and cytokinins. It will summarize and discuss their tissue- and cell-type specific distributions at the cellular and subcellular levels.
Keywords: Cytokinins; cytokininy; biologický transport; Plant Development; Intracellular Space; kyseliny indoloctové; Plant Physiological Phenomena; Biological Transport; Indoleacetic Acids; Organelles; vývoj rostlin; Metabolic Networks and Pathways; regulátory růstu rostlin; subcellular level; Plant Cells; auxin; phytohormone transport; homeostáza; organely; intracelulární prostor; phytohormone metabolism; cellular level; fyziologie rostlin; rostlinné buňky; Plant Growth Regulators; cytokinin; metabolické sítě a dráhy; Homeostasis